2020
DOI: 10.3390/clockssleep2010009
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of FIFO/DIDO Workers Being Home versus Away on Sleep and Loneliness for Partners of Australian Mining Workers

Abstract: Fly in Fly out/Drive in Drive out (FIFO/DIDO) is a prevalent work arrangement in the Australian mining industry and has been associated with adverse outcomes such as psychological stress, sleep disturbances, fatigue, and work/life interference. FIFO/DIDO work arrangements have the potential to not only impact the FIFO/DIDO worker, but also the partner of the FIFO/DIDO worker. However, there is sparse empirical evidence on the impact of FIFO/DIDO work arrangements on partners' sleep and subsequent performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The characteristics of the selected studies are shown in Table 2. Regarding the origin of the studies, one was conducted in Germany (STIELER, HUNGER, SEIBT, 2022), one in India (VIDYA et al, 2019) and one in Australia (WILSON et al, 2020). The study from India (VIDYA et al, 2019) did not specify which industries the shift workers came from, but the studies from Germany (STIELER, HUNGER, SEIBT, 2022) and Australia (WILSON et al, 2020) evaluated workers from the hotel/restaurant industry and mining, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the selected studies are shown in Table 2. Regarding the origin of the studies, one was conducted in Germany (STIELER, HUNGER, SEIBT, 2022), one in India (VIDYA et al, 2019) and one in Australia (WILSON et al, 2020). The study from India (VIDYA et al, 2019) did not specify which industries the shift workers came from, but the studies from Germany (STIELER, HUNGER, SEIBT, 2022) and Australia (WILSON et al, 2020) evaluated workers from the hotel/restaurant industry and mining, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In the German study (STIELER, HUNGER, SEIBT, 2022) the researchers showed that there was no difference in the quality of sleep of industrial workers when compared between work shifts. On the other hand, the Indian (VIDYA et al, 2019) and Australian (WILSON et al, 2020) studies reported that industrial workers who worked shifts or for long periods (away from home) had poorer sleep quality. In addition, the Australian study (WILSON et al, 2020) reported that workers who work away from home for long periods (≥14 days) experience greater daytime sleepiness and moderate to extreme loneliness symptoms (University of California, Los Angeles Loneliness Scale).…”
Section: Resultsmentioning
confidence: 99%
“…Shift work has inherent challenges in balancing social responsibilities (eg, household chores, time spent with family) while maintaining employment. 74 75 This intersection between familial responsibilities and work routines interferes with sleep hygiene and the time allocated to getting adequate sleep. 76 Therefore, future research may also consider the human factors which assist or impinge on shift workers’ capacity to actively implement sleep hygiene practices to achieve better sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Mitigating cognitive and safety risks is essential as night work has benefits for individuals and industries. Long blocks of night work are economically advantageous, particularly for operations such as mining or solar plant stations, where frequently flying staff in and out to maintain plant operations is not feasible 21 . On the other hand, employees often view greater work availability, salary, and family event attendance as an important trade-off for reduced sleep hours and poor sleep quality during their night shift rotations 22 .…”
Section: Introductionmentioning
confidence: 99%